Hubungan Gangguan Tidur Ibu Nifas Dengan Kejadian Postpartum Blues Di Wilayah Kerja Puskesmas Karangmalang Sragen - Amalia Nabillah Hasna; Murwati Murwati; Dewi Susilowati (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background : Postpartum mothers who fail to adjust to their new role can experience postpartum blues. Physical fatigue due to the activity of babysitting, breastfeeding, bathing the baby, cradling the baby at any time can cause maternal rest so that the mother's sleep/ rest can be disrupted. Rest/ sleep that is sufficient can reduce the occurrence of postpartum blues in postpartum mothers. Method: This study is an analytical study with a cross sectional approach. The population in this study were all postpartum mothers in the working area of Karangmalang Sragen health center. The sampling technique was purposive sampling and a sample of 31 postpartum mothers from day 3 to day 10 was obtained which had a history of spontaneous normal labor. Univariate analysis with frequency distribution and bivariate analysis with Rankspearman statistical test. The results of this study were the age of respondents at most,namely age 20-35 years 90.3%, multipara mothers 54.8%, respondents with secondary education 61.3%, mothers working at home 77.4%, severe sleep disorders 25.8%, experienced postpartum blues 32.3%. Result: The results of Rank-spearman statistical test can be concluded p value = 0,000 and r value of 0.812. onclusion: The conclusion is that there is a relationship between postpartum blues sleep disturbance in the working area of Karangmalang Sragen Health Center.